Fractional power NARX model identification using a harmony search algorithm - Wei, Hua-Liang; Zhao, Yifan; Billings, Stephen A.; Zhao, Jia (Cranfield University, 2012)
A novel type of discrete-time fractional-powernonlinear autoregressive with exogenous input (FPNARX) modelis introduced for system identification, modeling and prediction.Parameter estimation of such a model is a nonlinear optimizationproblem. A harmony search algorithm is then applied to solvesuch fractional models. Examples of both simulated and real dataare provided.